THE EFFECTIVENESS OF SIMULATION BOARD GAME TO IMPROVE SPEAKING SKILL IN DESCRIPTIVE TEXT TO THE TENTH GRADE STUDENTS OF SMA NEGERI 2 WONOSOBO 2015/2016 - Larasati, Nuari; Faridi, Abdurrachman; ., Rohani (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
This experimental research aims to find out if Simulation Board Game is moreeffective than Conventional Method to improve students’ speaking skill.Around sixty-six students of the tenth grades of SMA Negeri 2 Wonosobo, inacademic year 2015/2016 participating in this research were categorized intotwo groups named experimental and control group. To make it easier tounderstand, the result was presented in the form of statistical data. The post-testscore of both groups is quite far which is 75.12 for the experimental and 60.12for the control group. In addition, the sig (2-tailed) of the T-test which is 0.000explains that there is a significant difference between the students who aretaught by using Board Game and those who are taught by using Conventionalmethod. Furthermore, the N-gain score shows that the effectiveness of speakingskill with Board Game is at the medium level, while the effectiveness ofspeaking skill with Conventional method is at the low level. Based on the dataanalysis result of the research, it can be concluded that use of Board Game ismore effective than the use of Conventional method to teach speaking skill tothe students.